Energy Efficient Building Morphology for Indian Climatic Zones: Assessing the Reliability of Compactness Indicators for Evaluating Energy Efficiency in Indian Climatic Zones (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Certain energy related building standards make use of simple numeric indicators to describe a building's geometric compactness. Typically, such indicators make use of its surface area. the indicators are than used along with information on. the thermal transmittance of the building enclosure element to relevant thermal insulation criteria .Using extensive parametric thermal simulations ,this paper examines the reliability of such simple compactness indicators for energy-related evaluative assessments given that building with the same compactness attribute could differ in enclosure transparency ,orientation, morphology and shading in Indian five climatic zones i.e . Hot and Dry, Warm and Humid Temperate Cold Composite.